A qualitative examination of factors underlying transitions in problem gambling severity: Findings from the Leisure, Lifestyle, & Lifecycle Project. (3rd September 2017) - Mutti-Packer, Seema; Kowatch, Kristy; Steadman, Rodney; Hodgins, David C.; el-Guebaly, Nady; Casey, David M.; Currie, Shawn R.; Williams, Robert J.; Smith, Garry J.
Abstract: Background: The current study sought to explore the narrative accounts of individuals who underwent changes in their problem gambling severity, and identify subjective factors underlying these transitions. Additionally, respondents' perceived change in their gambling behavior was compared with a validated measure of problem gambling severity. Methods: Participants were recruited from The Leisure, Lifestyle, & Lifecycle Project (LLLP), a prospective cohort study based in Alberta, Canada. In-depth, semi-structured telephone interviews were conducted with a subset of participants identified as showing a significant increase or decrease in problem gambling severity between Wave 4 and 5 of the LLLP ( n = 41). Principles of phenomenology and grounded theory were used to thematically code interviews. Results: About half of respondents increased in problem gambling severity between Wave 4 and 5 ( n = 22), while 19 respondents decreased. For those who perceived this change ( n = 13), the most common factors underlying increases in problem gambling severity were the same factors underlying decreases and included financial, social, and internal reasons. More than half of the sample ( n = 28) perceived stability in, or a change in their gambling behavior that was incongruent with their problem gambling severity score. These respondents tended to endorse a greater degree of gambling fallacies, dissonant feelings, and mental health issues, compared to those who had accurately perceived their change. Conclusions: The findings suggest that many individuals may not accurately perceive transitions in their gambling. Gambling fallacies and dissonant feelings seem to underlie this discrepancy, highlighting the need for public health initiatives to focus on correcting these erroneous beliefs.